An Analysis of Code-Switching on The Utterances of Agnes Mo on Daniel Mananta Network's Youtube Channel - Ryeo, Park Jin; Wicaksono, Andri; Rahmawati, Dwi; Yani, Novi; Sari, Lusi Purnama (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2023)
This research aimed to analyze the phenomena of Code-Switching which examines the types and reasons for using code-switching used Agnes Monica on Daniel Mananta Network's YouTube channel entitled